2015
DOI: 10.1038/modpathol.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Uterine smooth muscle tumor analysis by comparative genomic hybridization: a useful diagnostic tool in challenging lesions

Abstract: The diagnosis and management of uterine smooth muscle tumors with uncertain malignant potential (STUMP) is often challenging, and genomic data on these lesions as well as on uterine smooth muscle lesions are limited. We tested the hypothesis that genomic profile determination by array-CGH could split STUMP into a benign group with scarce chromosomal alterations akin to leiomyoma and a malignant group with high chromosomal instability akin to leiomyosarcoma. Array-CGH genomic profile analysis was conducted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 21 publications
1
47
1
1
Order By: Relevance
“…In a recent multicenter European study, which included cases from 12 tertiary centers in France, Belgium, and the Czech Republic, 29 cases with an initial diagnosis of uterine STUMP were centrally reviewed by 2 gynecopathologists, and full agreement was obtained in only 7 (24.1%) of 29 cases. 9 The remaining cases were reported as LMS (n = 5) and benign leiomyoma variants (n = 17) after slide review. The discrepancy was due to the appreciation of the necrosis type (hyaline versus TCN) in 16 of 22 cases and the extent (focal or diffuse) and degree of nuclear atypia in the remaining 6 of 22 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent multicenter European study, which included cases from 12 tertiary centers in France, Belgium, and the Czech Republic, 29 cases with an initial diagnosis of uterine STUMP were centrally reviewed by 2 gynecopathologists, and full agreement was obtained in only 7 (24.1%) of 29 cases. 9 The remaining cases were reported as LMS (n = 5) and benign leiomyoma variants (n = 17) after slide review. The discrepancy was due to the appreciation of the necrosis type (hyaline versus TCN) in 16 of 22 cases and the extent (focal or diffuse) and degree of nuclear atypia in the remaining 6 of 22 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a European multicenter study, 9 array comparative genomic hybridization analysis allowed discriminating between STUMPs having scarce chromosomal alterations, akin to benign leiomyomas, and STUMPs with extensive chromosomal modifications similar to LMSs. The investigators showed that STUMPs with a relatively higher genomic index had more recurrences and unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-seven formalin-fixed and paraffinembedded uterine smooth muscle lesions from 76 patients (for one patient, both the primary tumor and the recurrence were examined) were collected in France through the French sarcoma network ( 17 were included in the series. The tumors were diagnosed between 1977 and 2013.…”
Section: Tumor Samplesmentioning
confidence: 99%
“…A few years ago, we published a new classification method based on genomic profiling complementary to the morphology able to distinguish within the STUMP category those uterine smooth muscle lesions with a risk of recurrence and poor outcomes from benign lesions. 17 In this study, we analyzed the genomic profile by array-comparative genomic hybridization in a series of 77 uterine smooth muscle lesions (44 leiomyosarcomas, 14 STUMP and 19 leiomyomas) to validate the power of genomic index as a recurrence predictor. Furthermore, we set out to improve our previous results by studying a larger series with a broader follow-up and to identify overall survival prognostic factors in uterine leiomyosarcomas.…”
mentioning
confidence: 99%
“…Tumors short on these criteria are diagnosed as smooth muscle tumors of uncertain malignant potential. 6,26,27 Molecular data are available for uterine spindle cell leiomyosarcomas and leiomyosarcomas in soft tissues demonstrating variable cytogenetically complex numerical and structural changes of tumors, highlighting the degree of genomic instability. 28,29 Frequent loss of heterozygosity particularly for chromosomes 10 and 13 has been described.…”
Section: Introductionmentioning
confidence: 99%